Physician associates and GPs in primary care: a comparison - Drennan, VM; Halter, M; Joly, L; Gage, H; Grant, RL; Gabe, J; Brearley, S; Carneiro, W; de Lusignan, S (Royal College of General Practitioners, 2015)
Background: Physician associates [PAs] (also known as physician assistants) are new to the NHS and there is little evidence concerning their contribution in general practice. Aim: This study aimed to compare outcomes and costs of same-day requested consultations by PAs with those of GPs. Design and setting: An observational study of 2086 patient records presenting at same-day appointments in 12 general practices in England. Method: PA consultations were compared with those of GPs. Primary outcome was re-consultation within 14 days for the same or linked problem. Secondary outcomes were processes of care. Results: There were no significant differences in the rates of re-consultation (rate ratio 1.24, 95% confidence interval [CI] = 0.86 to 1.79, P = 0.25). There were no differences in rates of diagnostic tests ordered (1.08, 95% CI = 0.89 to 1.30, P = 0.44), referrals (0.95, 95% CI = 0.63 to 1.43, P = 0.80), prescriptions issued (1.16, 95% CI = 0.87 to 1.53, P = 0.31), or patient satisfaction (1.00, 95% CI = 0.42 to 2.36, P = 0.99). Records of initial consultations of 79.2% (n = 145) of PAs and 48.3% (n = 99) of GPs were judged appropriate by independent GPs (P<0.001). The adjusted average PA consultation was 5.8 minutes longer than the GP consultation (95% CI = 2.46 to 7.1; P<0.001); cost per consultation was GBP £6.22, (US$ 10.15) lower (95% CI = −7.61 to −2.46, P<0.001). Conclusion: The processes and outcomes of PA and GP consultations for same-day appointment patients are similar at a lower consultation cost. PAs offer a potentially acceptable and efficient addition to the general practice workforce.